(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Literature reflects life and nature. This paper deals with analyzing the ecological themes in John Steinbeck’s The Log from the Sea of Cortez and can be a fascinating endeavor. This work, co-authored with marine biologist Edward Ricketts, combines Steinbeck’s literary prowess with a scientific exploration of the Gulf of California’s marine life. It delves into the interconnectedness of nature and human existence. The book emphasizes the importance of ecological understanding and conservation. It showcases Steinbeck’s keen observations of the natural world, highlighting how literature can contribute to ecological awareness and preservation. By examining this work, one can explore the intersection of literature and ecology, demonstrating how author like Steinbeck can raise ecological consciousness through his writing.